A reflection on critical reflection in professional education research - Winberg, Chris; Garraway, James; Engel-Hills, Penelope (Critical Studies in Teaching and Learning, 2023)
The roots of universities of technology can be traced back to technical colleges, which required compliance with industry standards, and the rule of labour markets. Universities of technology thus entered the university space, largely without an established critical tradition in teaching, learning, and research. This is the issue that we address in this paper, which is intended to inform potential authors in technical, vocational, and professional higher education who would like to publish their educational research studies in Critical Studies in Teaching and Learning (CriSTaL). The issue is important as universities of technology in South Africa are increasingly taking on the mantle of professional education, particularly in the fields of health, engineering, and applied sciences. In this paper, we discuss examples of published educational research that critique some of the ‘taken-for-granted’ ideas that have shaped the practices and aspirations of universities of technologies. The examples show that by judiciously drawing on traditions of critical reflective practice, and by bringing new ideas, concepts, and theories into educational research studies, further critical concepts can evolve. These new critical concepts will be of interest to the readers (and reviewers) of CRiSTaL, but more importantly could inspire universities of technology to reaffirm their connection to practice and begin to create a critical space for their own scholarly – and critical – identities.